Students' self-confidence in knisley mathematics learning with a constructivist approach - Oktafia, Mesi; Sari, Maila (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
Self-confidence among students majoring in Mathematics Education (Tadris Matematika) is a crucial aspect, given that they are future mathematics teachers. Observations reveal that 50% of second-semester Mathematics Education students at IAIN Kerinci exhibit low self-confidence, as evidenced by their difficulties in clearly defining problems. They also tend to lack ideas, struggle to eliminate inefficient alternatives, and face challenges in selecting the ideal options. Additionally, they often fail to recognize the impact of the solutions they choose. Therefore, a learning model that can enhance students' self-confidence is needed, such as the Knisley mathematics learning model with a constructivist approach. This study aims to examine the effect of the Knisley mathematics learning model with a constructivist approach on the self-confidence of Mathematics Education students at IAIN Kerinci. The study employed a quantitative method with an experimental approach. The population consisted of 34 second-semester Mathematics Education students at IAIN Kerinci. The instrument used was a self-confidence questionnaire. The results showed that the self-confidence of students who participated in the Knisley mathematics learning model with a constructivist approach was higher than that of students who followed the conventional learning model. Thus, the application of the Knisley mathematics learning model with a constructivist approach has a positive impact on the self-confidence of Mathematics Education students at IAIN Kerinci.